Human performance improvement : building practitioner competence - Rothwell, William J.; Hohne, Carolyn K.; King, Stephen B. (Houston : Gulf, 2000)
Serves as a tool that can be used to help build intellectual capital, establish and maintain a 'high-performance workplace, enhance profitability, and encourage productivity' - as well as increase return on equity and improved safety. This book shows you how to discover and analyze performance gaps; and plan improvements in human performance.
Includes bibliographical references and index.
oif 11/11/14
Loan
Keywords: Performance standards; Employees, training of evaluation; Employees